Last heroes: foot soldiers of Indian freedom - Sainath, P (India: penguin random house, 2022)
So who really spearheaded India's Freedom Struggle? Millions of ordinary people-farmers, labourers, homemakers, forest produce gatherers, artisans and others-stood up to the British. People who never went on to be ministers, governors, presidents, or hold other high public office.
Keywords: Indian Freedom